Clinical Outcomes and Health Care Utilization in Patients with Advanced Chronic Kidney Disease not on Dialysis After the Onset of the COVID-19 Pandemic in Ontario, Canada - Carol Wang; Yuguang Kang; Stephanie N. Dixon; Nivethika Jeyakumar; K. Scott Brimble; Amit X. Garg; Peter G. Blake; Therese A. Stukel; Matthew J. Oliver; Ahmed Al-Jaishi; Kristin K. Clemens; Longdi Fu; et al. (Canadian Journal of Kidney Health and Disease)
Background: The COVID-19 pandemic caused considerable disruption to health care services. Limited data exist on its impacts on clinical outcomes and health care utilization in patients with advanced chronic kidney disease (CKD). Objective: To compare the rates of all-cause mortality, cardiovascular-related hospitalizations, kidney-related outcomes, and health care utilization in patients with advanced CKD before and during the first 21 months of the COVID-19 pandemic. Design: Population-based, repeated cross-sectional study from March 15, 2017 to November 15, 2021, with follow-up until December 14, 2021 (preceding the Omicron variant). Setting: Linked administrative health care databases from Ontario, Canada. Participants: Adult patients with advanced CKD, defined as an estimated glomerular filtration rate <30 mL/min/1.73 m 2 (excluding patients receiving maintenance dialysis). Measurements: The pre-COVID-19 period was from March 15, 2017 to March 14, 2020 and the COVID-19 period was from March 15, 2020 to December 14, 2021. Poisson generalized estimating equations were used to predict post-COVID-19 patient outcomes and health utilization based on pre-COVID trends, estimating relative changes between the observed and expected outcomes. The multivariable model incorporated age group-sex interaction terms, a continuous variable denoting time in months to capture general trends, and pre-COVID month indicators to adjust for seasonal changes. Methods: Our primary outcome was all-cause mortality. Secondary outcomes included all-cause hospitalizations, non–COVID-19-related deaths and hospitalizations, intensive care unit (ICU) admissions, mechanical ventilation, and emergency room visits. We also examined cardiovascular-related hospitalizations, kidney-related outcomes, and ambulatory visits. Results: We included 101 688 adults with advanced CKD. The incidence of all-cause mortality was 147.4 (95% confidence interval [CI] = 145.1, 149.7) per 1000 person-years in the pre-COVID-19 period compared to 150.8 (95% CI = 147.9, 153.7) per 1000 person-years in the COVID-19 period. After adjustment, there was an 8% higher rate of all-cause mortality during the COVID-19 (adjusted relative rate [aRR] = 1.08, 95% CI = 1.03, 1.12). Non–COVID-19-related deaths did not increase substantially (aRR = 1.02, 95% CI = 0.97, 1.07). The COVID-19 period was associated with a lower rate of all-cause hospitalizations, ICU admissions, and emergency room visits. There were declines in long-term care admissions and non-nephrology physician visits in the first 3 months of the pandemic. In contrast, nephrology visits remained stable throughout the study period, including the first 3 months of the pandemic. Similarly, the monthly rates of acute kidney injury requiring dialysis initiation showed little variation compared with pre-pandemic levels. Limitations: Due to data availability at the time of analysis, we did not examine the impact of the COVID-19 pandemic on patients with advanced CKD beyond December 2021. Conclusions: Non–COVID-19-related deaths did not increase during the first 21 months of the pandemic, despite reduced health care utilization. The study informs health service planning in future health care emergencies.